Photoelastic analysis of all-on-four concept using different implants angulations for maxilla - Castelo Pedro Vemba CIDADE; Marcele Jardim PIMENTEL; Regiane Cristina do AMARAL; Mauro Antonio de Arruda NÓBILO; José Ricardo de Albergaria BARBOSA (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Conventional tilted implants are used in oral rehabilitation for heavily absorbed maxilla to avoid bone grafts; however, few research studies evaluate the biomechanical behavior when different angulations of the implants are used. The aim of this study was evaluate, trough photoelastic method, two different angulations and length of the cantilever in fixed implant-supported maxillary complete dentures. Two groups were evaluated: G15 (distal tilted implants 15°) and G35 (distal tilted implants 35°) n = 6. For each model, 2 distal tilted implants (3.5 x 15 mm long cylindrical cone) and 2 parallel tilted implants in the anterior region (3.5 x 10 mm) were installed. Photoelastic models were submitted to three vertical load tests: in the end of cantilever, in the last pillar and in the all pillars at the same time. We obtained the shear stress by Fringes software and found values for total, cervical and apical stress. The quantitative analysis was performed using the Student tests and Mann-Whitney test; p ≥ 0.05. There is no difference between G15 and G35 for total stress regardless of load type. Analyzing the apical region, G35 reduced strain values considering the distal loads (in the cantilever p = 0.03 and in the last pillar p = 0.02), without increasing the stress level in the cervical region. Considering the load in all pillars, G35 showed higher stress concentration in the cervical region (p = 0.04). For distal loads, G15 showed increase of tension in the apical region, while for load in all pillars, G35 inclination increases stress values in the cervical region.